Adverse Effects: Remarks on the “Scottish antidote” in the 15th Century - Clément Guézais (Revue LISA)
To underline the Scots’ success at the battle of Baugé in 1421, chronicler Walter Bower attributed the following remark to Pope Martin: Truly, the Scots are an antidote to the English. During the Wars of Independence, opposition to England had become a central component in the development of the Scottish national imagination. This attitude was reinforced during the Hundred Years War, when the international context favoured an alliance with France and the direct intervention of the Scots on the continent. The proverbial hostility to the English neighbour was an element of distinction which had undeniable advantages on an ideological level, but which also carried risks. This development provides a new perspective on the opportunities offered by the antagonism with England to define Scottish identity and reinforce its conspicuousness on the European stage, while also exploring the limits and negative aspects it conveyed according to continental authors.